2020
DOI: 10.12973/eu-jer.9.1.143
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Metacognitive Skills and Critical Thinking Skills at the Implementation of Four Different Learning Strategies in Animal Physiology Lectures

Abstract: The empowerment of metacognitive skills has an important role in increasing the capacity of critical thinking and active control of students' cognitive processes in learning. Metacognitive skills can be enhanced through the implementation of learning strategies involving higher-order thinking. The RQA, ADI, RQA integrated with ADI are constructivistic learning strategies that can accommodate these skills. The researches specifically examining the correlation between metacognitive skills and critical thinking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…However, based on the corrected mean scores, the QASEE learning model has the most potential in upgrading the preservice teachers' critical thinking skills, and then followed by the RQA learning model. This finding is in line with the research results by (Amin et al, 2020;Ichsan et al, 2019;Kwan & Wong, 2015;Mahanal et al, 2019;Prayogi et al, 2019;Sari et al, 2019;Zubaidah et al, 2018) who reported that critical thinking skills could be trained by conditioning individuals in constructivist-based learning environments through the implementation of certain learning models.…”
Section: Learning Models and Critical Thinking Skillssupporting
confidence: 90%
See 3 more Smart Citations
“…However, based on the corrected mean scores, the QASEE learning model has the most potential in upgrading the preservice teachers' critical thinking skills, and then followed by the RQA learning model. This finding is in line with the research results by (Amin et al, 2020;Ichsan et al, 2019;Kwan & Wong, 2015;Mahanal et al, 2019;Prayogi et al, 2019;Sari et al, 2019;Zubaidah et al, 2018) who reported that critical thinking skills could be trained by conditioning individuals in constructivist-based learning environments through the implementation of certain learning models.…”
Section: Learning Models and Critical Thinking Skillssupporting
confidence: 90%
“…Some of these aspects also appear in the RQA learning model. RQA learning model consisted of reading, summarizing, making questions, and answering questions that have been proven capable of empowering pre-service teachers' critical thinking skills (Amin et al, 2020;Thalib et al, 2017). Therefore, it is natural that the RQA learning model is found to be far more effective in improving the pre-service teachers' critical thinking skills than the conventional learning.…”
Section: Learning Models and Critical Thinking Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scientific literacy will be a provision for students in facing up complex global challenges (Hurd, 1998;Knain, 2015;Meldawati, 2017;Murnane et al, 2012). Meanwhile, critical thinking reinforces the students for being strong problem solvers (Amin et al, 2020;Saputro et al, 2020), impeccable decision makers and people who never stop learning (Florea & Hurjui, 2015;Moon, 2007;Ricketts, 2003). The critical thinking is also very important to be owned by each person (Hasan et al, 2019;Hayati & Berlianti, 2020;Maryuningsih et al, 2020;Permana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%